The relationship between leisure, income, and happiness: Comparing the labor-leisure trade-off and leisure satisfaction theory : DOI: 10.5937/etp2503001F - Fadilah Muhamad, Ichsan (Ekonomija - teorija i praksa, 2025)
This study compares two competing theories that explain the relationship among income, leisure, and happiness: the labor-leisure trade-off from microeconomics, which predicts a negative correlation between income and leisure time, and the leisure satisfaction theory from psychology, which predicts a positive correlation between leisure time and happiness. Using 2023 data from the UK Office for National Statistics, the study analyzes aggregated averages for five age groups through linear regression and Pearson's correlation in R software. The results reveal stronger positive correlations between leisure time and happiness (r up to 0.96) than negative correlations between income and leisure time (r up to -0.615), supporting the leisure satisfaction theory over the labor-leisure trade-off model. Although the small sample size and data aggregation limit the generalizability of findings, the results underscore the greater importance of leisure for well-being compared with income alone and highlight the need to integrate economic and psychological perspectives in research on subjective well-being.